Fetoplacental Weight Relationship in Normal Pregnancy and Pregnancy Complicated by Pregnancy-Induced Hypertension and Abruption of Placenta among Mothers Who Gave Birth in Southern Ethiopia, 2018 - Tsegaye Mehare; Daniel Kebede (Hindawi Limited, 2020)
Introduction. Placenta is a complex multifunctional organ that maintains pregnancy and promotes normal fetal development. The fetal outcome is adversely influenced by pathological changes in the placenta because it is a mirror that reflects the intrauterine status of the fetus. Placental abnormalities are considered a leading cause of maternal and prenatal mortality. This study aimed to assess the fetoplacental weight relationship in pregnancy-induced hypertension and abruption placenta and compare with the normal one. Objective. This study designed to assess fetoplacental weight relationships in normal pregnancy and pregnancy complicated by pregnancy-induced hypertension and abruption of placenta among mothers who gave birth in Dilla University Referral Hospital, southern Ethiopia, 2018. Materials and Methods. Institution-based comparative cross-sectional study was used on 50 placentas from mothers with pregnancy-induced hypertension, 50 placentas from mothers with abruption of placenta, and 50 placentas from mothers with normal pregnancy (control) with an age range of 19-34 years. The weight of the placenta and newborn were taken and the fetoplacental ratio was calculated. Results. Placental index as well as the weight of the newborn shows statistically significant (p<0.001) difference in pregnancy-induced hypertension and abruption placenta group compared with the normal group. The mean of the fetoplacental ratio in the normal group was 5.52 ± 0.07, in pregnancy-induced hypertension was 5.15 ± 0.11, whereas the abruption placenta was 4.99 ± 0.82. Conclusion. Both PIH and abruption placenta were associated with remarkable changes in the placenta index such as small placental weight and diameter and results in different kinds of congenital anomalies and low birth weight of the baby. Hence, fetoplacental ratio was altered. The lowest fetoplacental ratio was 4.99 for abruption placenta, and the highest was for a normal group of the placenta which was 5.52. Therefore, an examination of the placenta before and after birth guarantees for feto-maternal health.